Exploring the potential use of melatonin as a modulator of tramadol-induced rewarding effects in rats - Hakami, Alqassem Y.; Alghamdi, Badrah S.; Alshehri, Fahad S. (Frontiers in Pharmacology, 2024)
Background: Melatonin is responsible for regulating the sleep-wake cycle and circadian rhythms in mammals. Tramadol, a synthetic opioid analgesic, is used to manage moderate to severe pain but has a high potential for abuse and dependence.Studies have shown that melatonin could be a potential modulator to reduce tramadol addiction. Methods: Male Wistar rats were used to investigate the effect of melatonin on tramadol-induced place preferences. The rats were divided into four groups: control, tramadol, tramadol + melatonin (single dose), and tramadol + melatonin (repeated doses). Tramadol was administered intraperitoneally at 40 mg/kg, while melatonin was administered at 50 mg/kg for both the single dose and repeated-dose groups. The study consisted of two phases: habituation and acquisition. Results:Tramadol administration produced conditioned place preference (CPP) in rats, indicating rewarding effects. However, melatonin administration blocked tramadolinduced CPP. Surprisingly, repeated doses of melatonin were ineffective and did not reduce the expression of CPP compared to that of the single dose administration.The study suggests that melatonin may be a potential therapeutic option for treating tramadol addiction. The results indicate that melatonin attenuates the expression of tramadol-induced CPP, supporting its uses as an adjunct therapy for managing tramadol addiction. However, further studies are needed to investigate its effectiveness in humans.